KORELASI ANTARA KECERDASAN EMOSIONAL DENGAN HASIL BELAJAR IPA SISWA SEKOLAH DASAR NEGERI PONTIANAK - Fransisca, Melisa; Kresnadi, Hery; Asmayani, Asmayani (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2019)
AbstractThe general problem in this research is "Is there a correlation between emotional intelligence with learning outcomes in the Science lesson study class V 66 Pontianak City State Elementary School?". This research uses a descriptive method with a form of relationship study research. The population in this study were all fifth grade students of State Elementary School 66 Pontianak City. The sample in this research are 15 students grade VA and 15 students grade VB totaling 30 students drawn using probability sampling technique with simple random sampling type. Data collection tools and techniques used are indirect communication with a data collector in the form of a questionnaire and documentary study technique that is a data collector in the form of even semester report cards on Science subjects. The results showed emotional intelligence in Pontianak City 66 Elementary School was classified as good at 77.98%, and learning outcomes in subjects gained an average value of 76.97 is good because it goes in the 70-79 range. The values are then compared with r tablel at 5% for N = 30 is 0,316. Thus r count> from rtable or 0.413> 0.316, then Ha is accepted, which means that there is a correlation between emotional intelligence and learning outcomes in the Science lesson class V 66 Primary School Pontianak City.Keywords: Emotional intelligence , Learning Outcomes, Science.Â